Environmental Love Movement Through Environmental Poster Training, Waste Sorting Training and Organic Liquid Fertilizer Making - Reni Mulyani; Amalia Nur Milla (International Journal Of Community Service, 2024)
A healthy environment makes us less susceptible to various diseases Dengue fever, malaria, vomiting and other diseases. Not only in hygiene, environmental cleanliness also has a big influence. Comfort, beauty, and a beautiful environment ultimately bring peace. .The environmental movement carries out community service by educating waste sorting and waste management through seminars and workshops as well as environmental digital poster training. seminars and workshops as well as digital poster training for the environment to maintain a beautiful, clean and healthy environment. The purpose of the event was to encourage and educate the community to be able to handle waste, care, protect and love the environment as well as develop computerization skills. develop computerization skills. Methods of instilling the love movement the environment through waste sorting seminars, workshops on managing organic waste into liquid organic fertilizer, and training on making digital posters. organic waste into liquid organic fertilizer, and training in making digital posters by computerization. This community service increases the understanding of understanding of the community in separating organic, inorganic, and B3 waste, the community can practice and master the making of liquid organic fertilizer, and the community can make liquid organic fertilizer, can practice and master the making of liquid organic fertilizer, and can also campaign for the environment through posters. campaigning for the environment through digital posters.